THE IMPLEMENTATION OF SPATIAL PLANNING POLICIES IN REGIONS IN REALIZING GOAL NUMBER 11 OF THE SUSTAINABLE DEVELOPMENT GOALS - Diah Lestari; Endang Sutrisno; Iis Krisnandar (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
Spatial planning is a juridical instrument for environmental protection and management which is then used as one of the main focuses of the United Nations in the Sustainable Development Goals. However, Indonesia, which is currently focused on development and accelerating the investment, results in frequent actions that neglect the use of space and the environment. This formulation of the research is the problem regarding the implementation of spatial planning policies in the regions in order to realize goal number 11 of the Sustainable Development Goals. The purpose of this study is to examine the implementation of regional spatial planning policies in order to realize goal number 11 of the Sustainable Development Goals. The paradigm used is critical legal studies with qualitative research and using socio legal research approach. The results of the study found that problems regarding the implementation of goal number 11 of the Sustainable Development Goals in Majalengka Regency still meet some obstacles because Indonesia, which is currently focused on the development period and accelerating investment, made Regional Regulation Number 11 of 2011 concerning Spatial Plans for Majalengka Regency 2011-2031 no longer implementable as a policy product that has been implemented by the Regional Government of Majalengka Regency.